MicroRNA-431 regulates axon regeneration in mature sensory neurons by targeting the Wnt antagonist Kremen1 - Wu, Di; Murashov, Alexander K. (Frontiers in Molecular Neuroscience, 2013)
MicroRNAs are small, non-coding RNAs that function as key post-transcriptional regulators in neural development, brain function and neurological diseases. Growing evidence indicates that microRNAs are also important mediators of nerve regeneration, however, the affected signaling mechanisms are not clearly understood. In the present study, we show that nerve injury-induced miR-431 stimulates regenerative axon growth by silencing Kremen1, an antagonist of Wnt/beta-catenin signaling. Both the gain-of-function of miR-431 and knockdown of Kremen1 significantly enhance axon outgrowth in murine dorsal root ganglion (DRG) neuronal cultures. Using cross-linking with AGO-2 immunoprecipitation (CLIP), and 3′ untranslated region (UTR) luciferase reporter assay we demonstrate miR-431 direct interaction on the 3’-UTR of Kremen1 mRNA. Together, our results identify miR-431 as an important regulator of axonal regeneration and a promising therapeutic target.